Hydroclimatic influences on peatland CO2 exchange following upland forest harvesting on the Boreal Plains. Issue 8 (21st June 2016) - Plach, J.M.; Petrone, R.M.; Waddington, J.M.; Kettridge, N.; Devito, K.J.
Abstract: A comparative study of forest clear‐cut logging effects on daily growing season (May to October) net ecosystem CO2 exchange (NEE) of adjacent peatlands was conducted in two neighbouring forest upland‐peatland complexes over 4 years (2005 to 2008) on the Boreal Plains (BP) of Alberta, Canada. Higher vapour pressure deficit at the harvested‐upland (H‐U) peatland, reflecting increased turbulent mixing after adjacent upland forest removal (2007 and 2008), resulted in increased peatland evapotranspiration rates that contributed to a seasonal decline in soil moisture (volumetric moisture content) influencing NEE. Overall, a significant change in mid‐season NEE occurred at the H‐U peatland 1 year post‐harvesting, greater than NEE changes at the neighbouring intact‐upland peatland. However, 2 years post‐harvesting, mid‐season NEE returned to within range of pre‐harvesting variability (−0.54 to 1.34 g CO2 ‐C m −2 day −1 ). Results of this study demonstrate that BP peatland NEE is largely regulated by site‐specific water availability, which, in turn, may be influenced in the short term by shifting microclimate and soil moisture patterns because of clear‐cut logging. As such, predicting long‐term carbon storage function of BP peatlands will require careful consideration of changing hydroclimatic conditions because of rapid expansion of BP deforestation, given that these ecosystems already exist in a state of hydrologic risk in this moisture deficit eco‐region. Copyright © 2016 John Wiley & Sons, Ltd.